Dysbiosis of the intestinal microbiota in neurocritically ill patients and the risk for death - Ruoting Xu; Chuhong Tan; Jiajia Zhu; Xiuli Zeng; Xuxuan Gao; Qiheng Wu; Qiong Chen; Huidi Wang; Hongwei Zhou; Yan He; Suyue Pan; Jia Yin (Critical Care, 2019)
Abstract Background Despite the essential functions of the intestinal microbiota in human physiology, little has been reported about the microbiome in neurocritically ill patients. This investigation aimed to evaluate the characteristics of the gut microbiome in neurocritically ill patients and its changes after admission. Furthermore, we investigated whether the characteristics of the gut microbiome at admission were a risk factor for death within 180 days. Methods This prospective observational cohort study included neurocritically ill patients admitted to the neurological intensive care unit of a large university-affiliated academic hospital in Guangzhou. Faecal samples were collected within 72 h after admission (before antibiotic treatment) and serially each week. Healthy volunteers were recruited from a community in Guangzhou. The gut microbiome was monitored via 16S rRNA gene sequence analysis, and the associations with the clinical outcome were evaluated by a Cox proportional hazards model. Results In total, 98 patients and 84 age- and sex-matched healthy subjects were included in the analysis. Compared with healthy subjects, the neurocritically ill patients exhibited significantly different compositions of intestinal microbiota. During hospitalization, the α-diversity and abundance of Ruminococcaceae and Lachnospiraceae decreased significantly over time in patients followed longitudinally. The abundance of Enterobacteriaceae was positively associated with the modified Rankin Scale at discharge. In the multivariate Cox regression analysis, Christensenellaceae and Erysipelotrichaceae were associated with an increased risk of death. The increases in intestinal Enterobacteriales and Enterobacteriaceae during the first week in the neurological intensive care unit were associated with increases of 92% in the risk of 180-day mortality after adjustments. Conclusions This analysis of the gut microbiome in 98 neurocritically ill patients indicates that the gut microbiota composition in these patients differs significantly from that in a healthy population and that the magnitude of this dysbiosis increases during hospitalization in a neurological intensive care unit. The gut microbiota characteristics seem to have an impact on patients’ 180-day mortality. Gut microbiota analysis could hopefully predict outcome in the future.